Small-Scale and Large-Scale Modeling of Fiber-Reinforced Concrete Girders - Aleksandar Landović; Arpad Čeh; Anka Starčev-Ćurčin; Miloš Šešlija (Buildings)
Experimental and computational research on the behavior of small-scale and large-scale fiber-reinforced concrete (FRC) beams is presented in this paper. The experimental part included the small-scale bending tests, which were conducted on three 1.3 m long by 0.1 m wide by 0.15 m high rectangular simply supported beams, and the large-scale test that was conducted on 12.8 m long by 0.2 m wide by 1.3 m two-chords girder. The concrete mixture in the large-scale test was designed with environmentally more justifiable supplementary materials (binder and fibers), striving for sustainable excellence. To accurately predict the mechanical behavior of tested models, a numerical model incorporating the real nonlinear materials laws is used. A numerical model based on finite element analysis (FEA) is developed. The FEA model is created using a smeared crack approach with a constitutive law for the tensile behavior of FRC derived from an inverse analysis based on prism bending tests. The numerical model is validated against experimental results and the accuracy of numerical predictions based on finite element modeling showed a good correlation with the test data. The FEA-based model makes it easier to predict how FRC structures fail under transversal loading and can serve as a foundation for creating new design processes. Additionally, the presented research is aimed at the feasibility of recycled steel FRC field application in building structures. The usage of recycled steel fibers could achieve environmental benefits through the adoption of sustainable materials. The present study showcased the possibility of modeling reinforced concrete structural building parts made with recycled steel fibers using available software.